Irregular migrants and the law - Kassim, Azizah (Philippine Journal of Development)
This paper examines Malaysia`s policy on irregular migrants and its implementation, and discusses its impact. A survey and interview covering 404 respondents was conducted between July 2010 and June 2011 to ascertain the real situations surrounding irregular migrants in Malaysia, which is one of the major host countries of international migrants from developing nations. The policy on foreign workers was formulated in the mid-1980s to deal with the large number of irregular migrants and their many negative impacts, which had posed a serious challenge to the security, economy, and political stability of Malaysia.